Subcutaneous immunoglobulin 16.5% for the treatment of pediatric patients with primary antibody immunodeficiency - Gupta, Sudhir; Kobayashi, Roger H; Litzman, Jiří; Cherwin, Laurel; Hoeller, Sonja; Kreuwel, Huub (Expert review of clinical immunology, 2023)
INTRODUCTION: Human immunoglobulin (IG) administered intravenously (IVIG) or subcutaneously (SCIG) is used to prevent infections in patients with primary immunodeficiency diseases (PIDDs) such as primary antibody immunodeficiencies. AREAS COVERED: This review provides an overview of PIDD with a focus on SCIG treatment, including the properties and clinical trial results of a new SCIG 16.5% (Cutaquig, Octapharma) in pediatric patients. We also discuss the various benefits of SCIG including stable serum immunoglobulin G levels, high tolerability with fewer systemic side effects, and the flexibility of self-administration. EXPERT OPINION: Individualized treatment for PIDD in children is necessary given the different factors that affect administration of SCIG. Variables such as the dose, dosing interval, administration sites, and ancillary equipment can be adjusted to impact the long-term satisfaction with SCIG administration in pediatric patients. The successful work that has been conducted by both professional and patient organizations to increase awareness of PIDD, especially in pediatric patients, is substantial and ongoing. The importance of early diagnosis and treatment in the pediatric patient population cannot be overstated. The safety, efficacy, and tolerability of SCIG 16.5% have been demonstrated in pediatric patients with PIDDs providing an additional therapeutic option in this vulnerable population.
Keywords: Drug-Related Side Effects and Adverse Reactions; Immunoglobulin G; syndromy imunologické nedostatečnosti; Humans; intravenózní imunoglobuliny; Child; lidé; nežádoucí účinky léčiv; Immunoglobulins, Intravenous; Immunologic Deficiency Syndromes; dítě; imunoglobulin G; Infusions, Subcutaneous; subkutánní infuze